POWER AND INTERESTS IN INFORMATION AND COMMUNICATION AND DEVELOPMENT: EXOGENOUS AND ENDOGENOUS DISCOURSES IN CONTENTION†. (10th July 2011) - Mansell, Robin
Abstract This paper illustrates the persistence of an exogenous model of development that underpins many interventions aimed at employing information and communication technologies (ICTs) to meet development goals. The analysis is based on a sample of texts from reports produced by United Nations agencies and the World Bank. The aim is to show how the discourse on ICT interventions invariably is reminiscent of a dominant exogenous model even when alternative models with respect to development are seen to influence policy and practice. It is argued that practice‐based, emergence approaches offer an attractive, although insufficient, way forward. Copyright © 2011 John Wiley & Sons, Ltd.